The Man Behind the Mask: Accuracy and Predictors of Eyewitness Offender Descriptions. - Fahsing, Ivar A.; Ask, Karl; Granhag, Pär Anders (Journal of Applied Psychology, 2004)
An archival study was conducted using 250 offender descriptions by witnesses of armed bank robberies. The accuracy of the descriptions was gauged against authentic video documentation of the witnessed crimes. In general, witnesses provided accurate descriptions of the offenders but reported few identifying details. Multiple regression analyses revealed that the witnesses' role (bank tellers vs. customers), the type of weapon used, and the number of perpetrators involved were moderately predictive of the quality of offender descriptions. However, several of the observed relationships were conditional on whether descriptions of basic attributes (e.g., height, age, build) or more detailed features were considered. Hence, the authors concluded that verifying all aspects of witness descriptions is crucial when studying memories for actual crimes.